Studi Klasifikasi Tanah Metode USCS dan Pengaruh Kedalaman terhadap Karakteristik Tanah pada Lereng Lowwall Pit North PT Karya Putra Borneo - Ahmad Akmal Muhyiddin; Tommy Trides; Shalaho Dina Devi; Revia Oktaviani; Albertus Juvensius Pontus (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
This study aims to determine the soil classification of rock disintegration products based on the Unified Soil Classification System (USCS) and analyze its relation to sample depth variations on the lowwall slope of Pit North, PT Karya Putra Borneo, Kutai Kartanegara Regency, East Kalimantan. Soil samples were obtained through the Slake Durability test, simulating rock weathering from wetting and drying cycles, producing fine particles classified as weathered soil. These samples were analyzed for physical properties using Atterberg Limits tests and Grain Size Analysis. Observation point coordinates were X 508523.011 m, Y 9922791.186 m, at an elevation of 87.548 m. Drilling indicated soil material at 0–1.5 m depth; claystone with coal fragments at 2.97–4.44 m; siltstone with coal fragments at 4.44–10.55 m; and claystone at 12.05–29.36 m. USCS classification showed the materials were dominated by fine-grained soils: clay (CL) and silt (ML), with minor silty sand (SM). Correlation with borehole depth revealed no significant changes in soil classification, indicating that depth variations primarily affect soil physical properties rather than its classification type.